Identification of β-escin as a novel inhibitor of signal transducer and activator of transcription 3/janus-activated kinase 2 signaling pathway that suppresses proliferation and induces apoptosis in human hepatocellular carcinoma cells - Tan, S.M.-L. (2011)
10.1124/jpet.110.165498